System Performance of Opet: A Combined Optical and Pet Imaging System - Rannou-Fuentes, F (2012)
OPET is an imaging system that detects both highenergy ?-rays and optical wavelength photons. This system is capable of non-invasively and repeatedly imaging small animal models in-vivo for the presence of ?-rays from PET tracers and optical signals from bioluminescence. OPET consists of six detector modules arranged to form a ring with a bore diameter of 3.5cm, where each module is made up of a 64-channel multichannel photomultiplier tube (PMT) coupled to an 8×8 BGO crystal array. The crystal lengths and widths are 2.15mm x 2.15mm respectively. The crystal heights vary along the face of the PMT such that the array presents a smooth curving profile. The front surface of the crystals is left open to allow optical wavelength photons to enter the detector module. A charge-division readout circuit is implemented to decode the signals from the 64 outputs of each PMT into four signals from which position information is obtained. These signals are amplified, shaped, and digitized, and finally processed using a field programmable gate array (FPGA). Flood images are used to obtain position look-up tables as well as pulse height spectra for each crystal in both PET and Optical mode operation. Basic system performance parameters have been measured for both operation modes of OPET including: sensitivity and count-rate performance. In PET mode the system has a sensitivity of 3.5% at the center of the field of view and an energy resolution around 36%. The sensitivity for optical wavelength photons was measured for each detector using a calibrated light source and varied from 0.6% to 2.0%. The maximum count rate in Optical mode is 106 cps per detector. The first dual-mode data acquisition of OPET was performed using a two chamber phantom. In one chamber was a set of six 0.8mm diameter rods filled with FDG, while the other chamber was filled with an enzyme and substrate used in bioluminescence studies of small animals. Images from both modes of operation are be presented. © 2011 IEEE.